PERBEDAAN PENGARUH MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DENGAN TEAMS GAMES TOURNAMENT (TGT) TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MUATAN PELAJARAN IPS SISWA KELAS 4 SD - Magnifikat Iga Tobia; Firosalia Kristin (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2020)
This study attempts to know whether there are significant differences between the learning model STAD (Student Team Achievement Division) with learning model TGT (Teams Games Tournament). This study using quasi experiments and research done by design The Statics Group Pretest - Posttest Design. To the method used in collecting data with sheets of observation and test. The technical data analysis in by conducting (uji-t) , aimed at to know and measuring the difference of the capacity to think critical of charge lessons social class. The result of research conducted use (uji-t), The sig obtained the results (2-tailed) of 0,046, because the sig (2-tailed) not greater than 0,05 (0,046 < 0,05). Then Ho denied said there is no significant differences between the application of the learning model STAD (Student Team Achievement Division) with the application of a model of learning TGT (Teams Games Tournament) against a student of critical thinking skills social class from students 4th grade and Ha accepted said there is the existence of a significant difference between learning model STAD (Student Team Achievement Division) with a model of learning TGT (Teams Games Tournament) against a student of critical thinking skills social class from students 4th grade. Based on the research and discussion can be concluded that there is a significant difference between the application of a model of learning STAD (Student Team Achievement Division) with a model TGT (Teams Games Tournament) on a social class studies from students.4th grade primary school.